Lipid rafts regulate the lamellipodia formation of melanoma A375 cells via actin cytoskeleton-mediated recruitment of β1 and β3 integrin - Bi, Jiajia (Oncol Lett, 2018)
Lipid rafts, distinct liquid-ordered plasma membrane microdomains, have been shown to regulate tumor cell migration by internalizing and recycling cell-surface proteins. The present study reports that lipid rafts are a prerequisite for lamellipodia formation, which is the first step in the processes of tumor cell migration. The results from the wound-healing assay and immunostaining indicated that lipid rafts were asymmetrically distributed to the leading edge of migrating melanoma A375 cells during lamellipodia formation. When the integrity of lipids rafts was disrupted, lamellipodia formation was inhibited. The investigation of possible molecular mechanisms indicated that lipid rafts recruited β1 and β3 integrins, two important adhesion proteins for cell migration, to the lamellipodia. However, the different distribution characteristics of β1 and β3 integrins implied disparate functions in lamellipodia formation. Further immunostaining experiments showed that the actin cytoskeleton was responsible for lipid raft-mediated β1 and β3 integrin distribution in the lamellipodia. Together, these findings provide novel insights into the regulation of lipid rafts in lamellipodia formation, and suggest that lipid rafts may be novel and attractive targets for cancer therapy.